Gallbladder cancer: epidemiology and outcome - Hundal, Rajveer; Shaffer, Eldon A (Clinical epidemiology, 2014)
Gallbladder cancer, though generally considered rare, is the most common malignancy of the biliary tract, accounting for 80%-95% of biliary tract cancers. An early diagnosis is essential as this malignancy progresses silently with a late diagnosis, often proving fatal. Its carcinogenesis follows a progression through a metaplasia-dysplasia-carcinoma sequence. This comprehensive review focuses on and explores the risks, management, and outcomes for primary gallbladder carcinoma. Epidemiological studies have identified striking geographic and ethnic disparities - inordinately high occurrence in American Indians, elevated in Southeast Asia, yet quite low elsewhere in the Americas and the world. Age, female sex, congenital biliary tract anomalies, and a genetic predisposition represent important risk factors that are immutable. Environmental triggers play a critical role in eliciting cancer developing in the gallbladder, best exemplified by cholelithiasis and chronic inflammation from biliary tract and parasitic infections. Mortality rates closely follow incidence; those countries with the highest prevalence of gallstones experience the greatest mortality from gallbladder cancer. Vague symptoms often delay the diagnosis of gallbladder cancer, contributing to its overall progression and poor outcome. Surgery represents the only potential for cure. Some individuals are fortunate to be incidentally found to have gallbladder cancer at the time of cholecystectomy being performed for cholelithiasis. Such an early diagnosis is imperative as a late presentation connotes advanced staging, nodal involvement, and possible recurrence following attempted resection. Overall mean survival is a mere 6 months, while 5-year survival rate is only 5%. The dismal prognosis, in part, relates to the gallbladder lacking a serosal layer adjacent to the liver, enabling hepatic invasion and metastatic progression. Improved imaging modalities are helping to diagnose patients at an earlier stage. The last decade has witnessed improved outcomes as aggressive surgical management and preoperative adjuvant therapy has helped prolong survival in patients with gallbladder cancer. In the future, the development of potential diagnostic markers for disease will yield screening opportunities for those at risk either with ethnic susceptibility or known anatomic anomalies of the biliary tract. Meanwhile, clarification of the value of prophylactic cholecystectomy should provide an opportunity for secondary prevention. Primary prevention will arrive once the predictive biomarkers and environmental risk factors are more clearly identified.